Penerapan Model Solow: Kontribusi Modal dan Tenaga Kerja terhadap Pertumbuhan Ekonomi di Pulau Sumatera - Adipathy, Dina Arini; Novi Armunanto , Yohanes (Salam (Islamic Economics Journal), 2025)
The solow neoclassical growth model is a theoretical framework that emphasizes the role of capital accumulation, labor, and technological progress as the main determinants of growth and can measure the structure of economic growth on the island of Sumatra, which has good natural resource characteristics. This study analyzed 154 districts/cities in Sumatra using the quantitative methodology of pooled least square regression. Findings: The results of the study indicate that together government expenditure, investment, industry, and unemployment rates are very high in determining the variation in economic growth values ​​in Sumatra, namely 91.24% and the remaining 8.76% is determined by other variables. This indicates that the Solow Economic Growth model is quite well described in economic growth in Sumatra, although there are still variables that have a low influence. Keywords : Solow Economic Growth, Capital, Labor, Industry, Sumatra Island